First Clinical Consensus and National Recommendations on Tracheostomized Children of the Brazilian Academy of Pediatric Otorhinolaryngology (ABOPe) and Brazilian Society of Pediatrics (SBP), - Avelino,Melissa A.G. (2017)
Abstract Introduction: Tracheostomy is a procedure that can be performed in any age group, including children under 1 year of age. Unfortunately health professionals in Brazil have great difficulty dealing with this condition due to the lack of standard care orientation. Objective: This clinical consensus by Academia Brasileira de Otorrinolaringologia Pediátrica (ABOPe) and Sociedade Brasileira de Pediatria (SBP) aims to generate national recommendations on the care concerning tracheostomized children. Methods: A group of experts experienced in pediatric tracheostomy (otorhinolaryngologists, intensive care pediatricians, endoscopists, and pediatric pulmonologists) were selected, taking into account the different regions of Brazil and following inclusion and exclusion criteria. Results: The results generated from this document were based on the agreement of the majority of participants regarding the indications, type of cannula, surgical techniques, care, and general guidelines and decannulation. Conclusion: These guidelines can be used as directives for a wide range of health professionals across the country that deal with tracheostomized children.